Factors associated with increased lactate levels in cardiac surgeries: scoping review - Fernanda de Castro Teixeira; Thatiane Evelyn de Lima Fernandes; Karena Cristina da Silva Leal; Katia Regina Barros Ribeiro; Daniele Vieira Dantas; Rodrigo Assis Neves Dantas (Revista Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to map the factors associated with increased lactate levels in the postoperative period of cardiac surgery using extracorporeal circulation. Methods: this is a scoping review carried out in December 2022, across ten data sources. It was prepared in accordance with the recommendations of the Joanna Briggs Institute and the Preferred Reporting Items for Systematic Reviews and Meta Analyses Extension for Scoping Reviews checklist. Results: the most recurrent findings in studies regarding the factors responsible for the increase in lactate were: tissue hypoperfusion, cardiopulmonary bypass time and use of vasoactive drugs. In 95% of studies, increased lactate was related to increased patient mortality. Conclusions: discussing the causes of possible complications in cardiac surgery patients is important for preparing the team and preventing complications, in addition to ensuring quality recovery.